2020
DOI: 10.3390/ani10060973
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Amino Acid Supplementations to Low-Protein Diets: Effect on Performance, Carcass Yield, Meat Quality and Nitrogen Excretion of Finishing Broilers under Hot Climate Conditions

Abstract: The objective of this study was to evaluate the effect of low-protein diets with amino acid supplementation on growth performance, carcass yield, meat quality and nitrogen excretion of broilers raised under hot climate conditions during the finisher period. In trial 1, broilers from 28 to 49 days of age were fed 18% crude protein (CP) as a positive control or 15% CP supplemented with (1) DL-methionine (Met) + L-lysine (Lys), (2) Met + Lys + L-Arginine (Arg), or (3) Met + Lys + L-Valine (Val). In trial 2, broil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…An important issue that might affect poultry immunity, health, and performance is dietary constituents. Crude protein is the most expensive item in poultry nutrition, at both the protein level as well as the protein source; essential amino acids are crucial ( 68 , 69 ). Due to the nature of the poultry digestive tract, concentrated feeds are required, and essential amino acids rather than crude protein are vital.…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue that might affect poultry immunity, health, and performance is dietary constituents. Crude protein is the most expensive item in poultry nutrition, at both the protein level as well as the protein source; essential amino acids are crucial ( 68 , 69 ). Due to the nature of the poultry digestive tract, concentrated feeds are required, and essential amino acids rather than crude protein are vital.…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
“…Nowadays, poultry diets are formulated based on digestible amino acids rather than crude protein. This goal is achieved by supplementation with industrial amino acids such as methionine, lysine, arginine, tryptophan, and threonine to ensure adequate intake of limiting essential amino acids ( 68 70 ). Although substantial progress has been made on ideal amino acid requirements, the optimal levels for the development of immune organs, and thus immune function, requires further investigation ( 73 ).…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
“…Among different types of fat sources such as palm oil, coconut oil, soy oil and fish oil, Htin et al (2007) suggested the use of palm oil (Table 2). Also, and Attia, Bovera, et al (2020) recommended oil supplementation at 1.5% under hot climate.…”
Section: Feeding Approachesmentioning
confidence: 99%
“…Beside the challenges of feed quality (Bastianelli et al., 2005; Houndonougbo et al., 2012) and feed costs (Leeson & Summers, 2005; Omole et al., 2005), there is serious challenge of negative effect of high ambient temperature (Attia, Al‐Harthi, et al, 2020; Attia, Bovera, et al., 2020; Fathi et al., 2013; Khan et al., 2011; Mashaly et al., 2004; Muiruri & Harrison, 1991) which has posed a serious constraint to a profitable and sustainable broiler chicken production under hot and humid tropical climate. In fact, tropical conditions limit growth and performance of broiler chickens (Gordon & Charles, 2002; Renaudeau et al., 2012).…”
Section: Constraints To the Development Of Poultry Meat Industry Undementioning
confidence: 99%
“…Some authors reported that greater lysine or Arg:Lys ratios in broiler diets have a beneficial impact, whereas others showed an adverse effect at HT on gain and breast yield [72]. Therefore, dietary AA influenced heat generation [77] and improved broiler performance under high temperatures while decreasing nitrogen excretion by 21% between 28 and 49 days of age [78].…”
Section: Effect Of Hs On Amino Acidsmentioning
confidence: 99%